2010
DOI: 10.1161/circulationaha.109.897249
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incidence, Severity, and Outcome of Hospitalized Myocardial Infarction

Abstract: Background-In 2000, the definition of myocardial infarction (MI) changed to rely on troponin rather than creatine kinase (CK) and its MB fraction (CK-MB). The implications of this change on trends in MI incidence and outcome are not defined. Methods and Results-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
268
1
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 300 publications
(301 citation statements)
references
References 32 publications
24
268
1
8
Order By: Relevance
“…Despite the declining incidence of CHD in the USA reported in the former section of this article, many (26,(39)(40)(41), but not all (42,43), observational studies have found no reduction in the incidence of MI in a variety of time periods including 1971-1982 and 1982-1992 (26), 1975-1997 (39), 1994-1999 (40), and 1987-2006 (43). In a study of 5,832 Massachusetts patients with acute MI seen between 1975 and 1997, the incidence of MI was similar in 1975-1978 and 1997, respectively (230 per 100,000 people in both periods) (39).…”
Section: What About Mi?mentioning
confidence: 67%
“…Despite the declining incidence of CHD in the USA reported in the former section of this article, many (26,(39)(40)(41), but not all (42,43), observational studies have found no reduction in the incidence of MI in a variety of time periods including 1971-1982 and 1982-1992 (26), 1975-1997 (39), 1994-1999 (40), and 1987-2006 (43). In a study of 5,832 Massachusetts patients with acute MI seen between 1975 and 1997, the incidence of MI was similar in 1975-1978 and 1997, respectively (230 per 100,000 people in both periods) (39).…”
Section: What About Mi?mentioning
confidence: 67%
“…50 These profound changes are exemplified by a decline in the incidence of myocardial infarction, 51,52 a preponderance of non-ST-segment-elevation myocardial infarctions, and a shift in the mix of heart failure cases with more patients presenting with preserved ejection fraction. 53 The impact of this evolution is amplified by 2 key factors: incident manifestations of CVD occurring at older ages and the aging of the population, which leads to a larger pool of candidates for CVD.…”
Section: How Caregiving Costs Add To the Burden Of Heart Disease Andmentioning
confidence: 99%
“…Therefore, our findings should be confirmed in different racial and ethnic groups and in other data sets. Reflecting the changing epidemiology of MI, in which non-ST-segment elevation now constitutes most MI, 46,47 only 20% of our cohort presented with ST-segment elevation. Additional assessment of differential associations between cTnT and post-MI outcomes by MI type is therefore warranted.…”
Section: Figurementioning
confidence: 99%